Efecto de la línea genética y el sexo sobre el crecimiento en cuyes (Cavia porcellus) (2015)
ABSTRACT: The guinea pig (Cavia porcellus) represents an economic alternative with broad social acceptance in some areas of Colombia, therefore the analysis of productive performance of this species is of much interest for genetic selection programs. The aim of this work was to evaluate the effect of line and sex on body growth. Five-hundredth and forty-six records from the experimental station Botana, belonging to the University of Nariño, in Colombia were analyzed. The variables evaluated in the mother were: weight at parturition, parity and litter size; and for the pups: birth weight, weaning weight, weight at four, eight and twelve weeks of age. Data were analyzed by multivariate and univariate variance procedures with covariates, canonical orthogonal contrasts, Tukey contrasts, correlation analysis, frequency distribution, exploratory descriptive analysis and non- lineal regression. The results show that the number of pups by line fluctuated between 3.69 and 4.34. The correlation analysis showed an inverse relationship between litter size and individual weight at birth for lines 2 and 3, but there was a positive autocorrelation between all the weights at different ages. The evaluation of the sex effect on the corporal weight allowed to detect superiority for the males, especially in the lines 1 and 2. The analysis of non-lineal regression estimated bigger growth rates for the males, although this parameter and the mature weight were overestimated for both sexes. The covariable that most determined the weight of pups at different ages was the mother weight at parity.